Cover Picture: Using all our genomes: Blood‐based liquid biopsies for the early detection of cancer (View 1/2022). Issue 1 (31st January 2022) - Adams, Eddie; Sepich‐Poore, Gregory D.; Miller‐Montgomery, Sandrine; Knight, Rob
Abstract : The image of article number 20200118 depicts the diverse bloodborne tumor‐derived molecular cargo that can be sampled through a simple blood draw and harnessed for minimally invasive detection of cancers. These analytes consist of circulating tumor cells, tumor cell‐derived nucleic acids (DNA and RNA), exosomes, proteins, and – more recently appreciated – microbial nucleic acids derived from intratumoral microbes and other sources. Find out more about blood‐based detection of cancer in the Review Article by Eddie Adams et al.